2021
DOI: 10.1007/s10633-021-09857-5
|View full text |Cite|
|
Sign up to set email alerts
|

Electroretinogram responses in myopia: a review

Abstract: The stretching of a myopic eye is associated with several structural and functional changes in the retina and posterior segment of the eye. Recent research highlights the role of retinal signaling in ocular growth. Evidence from studies conducted on animal models and humans suggests that visual mechanisms regulating refractive development are primarily localized at the retina and that the visual signals from the retinal periphery are also critical for visually guided eye growth. Therefore, it is important to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 175 publications
3
18
0
Order By: Relevance
“…These findings are consistent with the previous mfERG investigations in different refractive errors that also reported significantly smaller mfERG amplitudes in myopes, which were associated with the degree of myopia, axial length and retinal eccentricity. 24 The previous studies reported that the reduced mfERG responses in myopes were related to reduced retinal thickness profile, 52 cone photoreceptor density, 50,51 retinal ganglion cell density, 53 monocular flicker modulation thresholds 54 and also localised structural alterations in eyes to increased…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These findings are consistent with the previous mfERG investigations in different refractive errors that also reported significantly smaller mfERG amplitudes in myopes, which were associated with the degree of myopia, axial length and retinal eccentricity. 24 The previous studies reported that the reduced mfERG responses in myopes were related to reduced retinal thickness profile, 52 cone photoreceptor density, 50,51 retinal ganglion cell density, 53 monocular flicker modulation thresholds 54 and also localised structural alterations in eyes to increased…”
Section: Discussionmentioning
confidence: 98%
“…Association between relative peripheral refraction and corresponding electro-retinal signals Satish Kumar Gupta 1 | Ranjay Chakraborty 2 | Pavan Kumar Verkicharla 1,3 The peripheral defocus-induced myopic changes appear to be mediated by a cascade of retinal responses at the level of the outer and inner retina. 3,23 Various studies have attempted to understand how these retinal responses at different retinal eccentricities in human eyes vary with refractive status using electrophysiological tests (see review by Gupta et al 24 ). Investigations with the multifocal electroretinogram (mfERG) indicated significantly smaller N1, P1 and N2 amplitudes in myopes than in non-myopes that were correlated with increasing axial length, the degree of myopia and retinal eccentricity.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…In support, several hypotheses such as decreased neural sample density, spectacle minification due to high‐powered lenses resulting in loss of resolution, low contrast sensitivity and decreased cone density were proposed as potential reasons for reduced visual acuity in the absence of ocular pathology 16–23 . Secondary to structural changes and axial elongation, myopic eyes undergo functional alterations compared with an emmetropic eye as represented by a reduction in the electroretinogram responses 24,25 …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Secondary to structural changes and axial elongation, myopic eyes undergo functional alterations compared with an emmetropic eye as represented by a reduction in the electroretinogram responses. 24,25 Various studies have reported that a certain proportion of individuals with high myopia had reduced bestcorrected visual acuity (BCVA); however, it is unclear from the previous literature what proportion of low to moderate myopes have reduced BCVA. 1,2,14,15 Considering that ocular stretching is a phenomenon that is not limited to highly myopic eyes and that pathologic myopia lesions can occur in low-moderate myopes (2.5%), 26 then it is critical to understand the factors associated with reduced visual acuity.…”
Section: Introductionmentioning
confidence: 99%